spektrum getaran pada bantalan elemen gelinding tanpa pelumasan dan mengalami misalignment - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Vibration spectrum for bearing failure in normal condition has been investigated by many researchers. This research done to investigate the life and vibration spectrum of ball bearing operated without lubrication and installed misalignmently. Two ball bearings operated wi/hout grease and vibration data recorded using pc-based instrumentation and s(?/iware I.ab VIEW. Measurement done in the radial direction and data recorded in 5 hours interval. Vibration spectrum of the specimens have different mode compared to normal specimen. The bearing s life is also reduced significantly.